PENGARUH PENGGUNAAN MODEL PROJECT BASED LEARNING TERHADAP HASILBELAJAR SENI RUPA DI SMP NEGERI 26 PADANG - DAYAT PUTRA PAHLAWAN, Drs. Yusron Wikarya, M.Pd. Drs. Wisdiarman, M.Pd. (Universitas Negeri Padang, 2017)
This study aims to now whether there is influence of the use of project based learning model of art learning outcomes in SMP Negeri 26 Padang. The type of research used is experiment with pre-test and post-test taking with Purposive Sampling. The research data was collected by the test of learning result that is the theory test and practice test. The findings in this study indicate that the learning outcomes of students using project based learning is better, when compared with using conventional models. This means that the use of project based learning in learning is needed by every educator to improve student learning outcomes especially in art and cultural arts subjects in SMP N 26 Padang.Keywords: Model of Project Based Learning, Learning Outcomes.